WeChat official accounts and their impact - Wang, Chenlu; Martínez- Rodrigo, Estrella; García-García, Francisco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The present research focuses on the role of "official accounts" on WeChat, designed for the dissemination of textual content in the Chinese language. Currently, it is the main channel for information dissemination in that language. The objective is to investigate changes in this function between 2020 and 2023, and their impact on the mode of production and dissemination of content. To achieve this goal, a qualitative comparative methodology has been used, comparing the services in the function as it was before 2020 and its current state in 2023. Specifically, innovations are classified into three aspects: content format, interaction, and text indicators. This study concludes that the evolution in this function has changed both the mode of textual production and its dissemination in society, warning of possible negative consequences caused by these changes.